Role of Microcredit to Empower Women in Bangladesh : An Investigation on two NGOs in Shariatpur District (Bangladesh Journal of Public Administration, 2025)
For decades, studies on women’s empowerment have concentrated on assessing the processes, effects, and obstacles linked to microfinance initiatives executed by non-governmental organisations (NGOs). Although several studies have demonstrated notable results, others have provided evidence of minimal or insignificant effects, rendering the efficacy of these programs a matter of contention. This study addresses a significant geographical gap by investigating the effects of microfinance programs on women’s empowerment in Shariatpur, one of Bangladesh’s least developed districts, where no previous research has been undertaken. This research assesses the eficacy of microcredit programs implemented by two local NGOs—Shariatpur Development Society and Naria Unnayan Samiti—in fostering personal, relational, and economic empowerment among women in Charmahiskali village. Both organisations have played a role in expanding access to microcredit and initiating community engagement activities; however, their overall impacts appear to be Limited in the long run due to structural and socio-cultural challenges. The study employed a qualitative technique, employing a two-fold data collection strategy that incorporates primary and secondary sources through content analysis, surveys, and in-depth interviews. It focusses on women who have availed microcredit multiple times to evaluate their ongoing development across ten essential indicators of empowerment. Findings reveals that, although microcredit program by two local NGOs has improved women’s self-confidence, familial respect, and involvement in household decision- making, its overall effect is limited. The majority of individuals utilized the loans for domestic expenditure, yielding no significant long-term advantages. Moreover, high interest rates, inadequate training, patriarchal norms, and persistent social obstacles diminish the capacity of these initiatives to achieve substantial empowerment. Thus, this research concludes that microfinance exerts a minimal influence on the empowerment of women in the studied region.